Advancing Health Workforce Education: Development and Psychometric Validation of the Challenges in Team-Based Learning Questionnaire (CTBLQ) in Vietnam - Pham Thi Kien; Leslie F Lazaro (Qualitative and Quantitative Research Center, 2026)
Although Team-Based Learning (TBL) is widely adopted in health professions education to strengthen collaborative competencies, instruments specifically designed to identify barriers to its implementation remain limited, particularly in transitioning educational contexts. This study aimed to develop and psychometrically validate the Challenges in Team-Based Learning Questionnaire (CTBLQ) among undergraduate nursing students in Vietnam. A methodological research design was employed involving 280 undergraduate nursing students selected through stratified simple random sampling. The 18-item questionnaire underwent expert content evaluation and linguistic review before reliability testing and exploratory factor analysis. The CTBLQ demonstrated excellent internal consistency (Cronbach’s α = 0.910), and all corrected item–total correlations exceeded the recommended threshold of 0.30. Sampling adequacy was confirmed by a Kaiser–Meyer–Olkin value of 0.853, while Bartlett’s test of sphericity was statistically significant (χ²(153) = 4098.257, p < 0.001). Exploratory factor analysis supported a three-factor structure explaining 68.10% of the total variance, comprising learning preparation, participation, and motivation challenges; interpersonal and social conflict challenges; and learning benefit and team harmony challenges. Overall, the CTBLQ demonstrated satisfactory psychometric properties and provides a standardized diagnostic instrument for identifying barriers to Team-Based Learning implementation. The instrument may support evidence-informed curriculum evaluation, educational planning, and future research in nursing education while contributing to the advancement of health workforce education through improved implementation of collaborative learning.